The Effects of Generative AI Platforms on Undergraduates' Narrative Intelligence and Writing Self-Efficacy - Nikolaos Pellas (MDPI AG, 2023)
Digital storytelling and generative artificial intelligence (AI) platforms have emerged as transformative tools that empower individuals to write with confidence and share their stories effectively. However, a research gap exists in understanding the effects of using such web-based platforms on narrative intelligence and writing self-efficacy. This study aims to investigate whether digital story creation tasks on web-based platforms can influence the narrative intelligence and writing self-efficacy of undergraduate students. A pretest-posttest comparison study between two groups was conducted with sixty-four undergraduate students (n = 64), majoring in Primary Education. More specifically, it compares the effects of the most well-known conventional platforms, such as Storybird, Storyjumper, and ZooBurst (control condition), and generative AI platforms, such as Sudowrite, Jasper, and Shortly AI (experimental condition) on undergraduate students, with an equal distribution in each group. The findings indicate that the utilization of generative AI platforms in the context of story creation tasks can substantially enhance both narrative intelligence scores and writing self-efficacy when compared to conventional platforms. Nonetheless, there was no significant difference in the creative identity factor. Generative AI platforms have promising implications for supporting undergraduates' narrative intelligence and writing self-efficacy in fostering their story creation design and development.